Hydrogeochemical Assessment of Groundwater Quality and its Suitability for Irrigation and Domestic Purposes in Rural Areas, North of Baiji City-Iraq - Abed, Mahmood F.; Zarraq, Ghazi; Ahmed, Salwa H. (Iraqi Journal of Science, 2021)
Background: The present study was conducted to highlight the importance of environmental pollution and its negative impacts on aquatic, plants and animals lives, especially in industrial areas. Objective: This research involved studying the hydrogeochemistry of the groundwater and assessing its quality for irrigation and domestic purposes using quality parameters. In this study, 33 groundwater samples were collected from wells during May 2013 and were analyzed for major ions and TDS. Results: The hydrogeochemical facies of groundwater were identified using the Gibbs model and Chloro – alkaline indices. The results of the Gibbs graph suggest that groundwater chemistry is controlled by evaporation factors. It was found that the values of chloro – alkaline indices were positive, indicating ionic exchange between Na+ in groundwater with Ca2+ and Mg2+ in the aquifer material. Conclusion: The current study of corrosivity ratio showed that groundwater wells are unsuitable for domestic uses.